Local envenomation from the bite of a juvenile false water cobra (Hydrodynastes gigas; Dipsadidae). (1st March 2016) - Keyler, D.E.; Richards, D.P.; Warrell, D.A.; Weinstein, S.A.
Abstract: The false water cobra ( Hydrodynastes gigas ) is a non-front-fanged colubroid snake frequently exhibited in zoos, and maintained by amateur collectors. Little detailed documentation regarding the time-course of symptoms development and the consequences of their bites to humans has been published. Reported here is a case of envenoming in a 25 yo male that occurred after the bite of a juvenile H. gigas . The victim was bitten on the fourth digit of the left hand while processing the snake for sex determination, and the snake remained attached to the digit for approximately 30 s; there was no jaw advancement. Within 5 min, intense local pain developed, and at 4hr post bite the entire dorsal aspect of the hand was significantly edematous, The local effects progressed and involved the entire forearm, and the local pain referred to the axillary region. Mild paresthesia and local blanching ("pallor") were noted in the affected digit, but resolved within 7 days. The clinical course in the patient showed that moderate localized symptoms may result from the bite of a juvenile H . gigas . Highlights: A unique case of envenomoming by a juvenile Hydrodynastes gigas is presented. H. gigas envenomation compared to that of other snake species is discussed. The bite by H. gigas did not result in serious medical consequences.